Association Between Preeclampsia Risk and Fine Air Pollutants and Acidic Gases: A Cohort Analysis in Taiwan - Shih-Yi Lin; Shih-Yi Lin; Yu-Cih Yang; Yu-Cih Yang; Jun-Wei Su; Jun-Wei Su; Jie-Sian Wang; Jie-Sian Wang; Chang-Cheng Jiang; Chang-Cheng Jiang; Chung-Y. Hsu; Chia-Hung Kao; et al. (Frontiers Media S.A., 2021)
Background: Fine air pollutant particles have been reported to be associated with risk of preeclampsia. The association between air pollutant exposure and preeclampsia risk in heavily air polluted Taiwan warrants investigation.Methods: We combined data from Taiwan National Health Insurance (NHI) Research Database (NHIRD) and Taiwan Air Quality Monitoring Database. Women aged 16-55 years were followed from January 1, 2000, until appearance of ICD-9 coding of preeclampsia withdrawal from the NHI program, or December 31, 2013. Daily concentration of NOx, NO, NO2, and CO was calculated by Kriging method. The Cox proportional hazard regression model was used for risk assessment.Results: For NOx, Relative to Quartile [Q] 1 concentrations, the Q2 (adjusted hazard ratio adjusted = 2.20, 95% CI = 1.50-3.22), Q3 (aHR = 7.28, 95% CI = 4.78-11.0), and Q4 (aHR = 23.7, 95% CI = 13.7-41.1) concentrations were associated with a significantly higher preeclampsia or eclampsia risk. Similarly, for NO, relative to Q1 concentrations, the Q2 (aHR = 1.82, 95% CI = 1.26-2.63), Q3 (aHR = 7.53, 95% CI = 5.12-11.0), and Q4 (aHR = 11.1, 95% CI = 6.72-18.3) concentrations were correlated with significantly higher preeclampsia or eclampsia risk. Furthermore, for NO2, relative to Q1 concentration, the Q2 (aHR = 1.99, 95% CI = 1.37-2.90), Q3 (aHR = 6.15, 95% CI = 3.95-9.57), and Q4 (aHR = 32.7, 95% CI = 19.7-54.3) concentrations also associated with a significantly higher preeclampsia or eclampsia risk.Conclusion: Women exposed to higher NOX, NO, NO2, and CO concentrations demonstrated higher preeclampsia incidence.